ANALISA STATIC STRESS TURBIN AIR ALIRAN PIPA DENGAN METODE CFD - Daniel Joachim; Fathurrahman Fathurrahman; Silvester Lam; M. Sobron Yamin Lubis (PROSIDING SERINA, 2021)
Turbine is a rotating machine that takes energy from a fluid flow. A water turbine is a machine that converts the potential energy of air into mechanical energy. Indonesia has many water areas such as rivers, streams, seas, and so on. Unfortunately, the development of new and renewable energy in Indonesia has not been maximized. Based on this, the team designed a turbine in a pipe called Tulipa. An innovation to exploit the potential of new and renewable energy. Tulipa utilizes the wastewater flow in the factory that is not used and then converts it back into electrical energy. The energy produced by Tulipa is 5,593 kW. The calculations in this study become the calculation of the strength of the rods and simulations. Tulipa was tested using mechanical analysis of each component. The analysis was performed using Fusion 360 software for mechanical simulation and ANSYS for CFD or Computational Fluid Dynamic simulation. Simulations were carried out to determine the value of static stress, reaction force, turbulence, velocity, pressure, and density. The compressive force used is 30N in each section with the load being evenly distributed and the fluid velocity used in the CFD is 4m/s.Turbin adalah mesin berputar yang mengambil energi dari aliran fluida. Turbin air adalah mesin yang mengubah energi potrensial air menjadi energi mekanik. Indonesia memiliki banyak sekali wilayah perairan seperti sungai, kali, laut, dan lain sebagainya. Sayangnya pengembangan energi baru terbarukan di Indonesia belum maksimal. Berdasarkan hal tersebut, tim merancang sebuah turbin di dalam media berupa pipa yang bernama Tulipa. Sebuah inovasi untuk memanfaatkan potensi dari energi baru terbarukan. Tulipa memanfaatkan aliran pembuangan limbah cair pada pabrik yang tidak terpakai kemudian mengubahnya kembali menjadi energi listrik. Energi yang dihasilkan Tulipa sebesar 5.593 kW. Perhitungan pada penelitian ini dibagi menjadi perhitungan kekuatan rangka batang dan simulasi. Tulipa diuji dengan menggunakan analisa mekanikal dari masing-masing komponen. Analisa dilakukan menggunakan Software Fusion 360 untuk simulasi mekanikal dan ANSYS untuk simulasi CFD atau Computational Fluid Dynamic. Simulasi dilakukan untuk mengetahui nilai static stress, reaction force, turbulency, velocity, pressure, dan density. Gaya tekan yang digunakan adalah 30N pada tiap bagian dengan beban terdistribusi secara merata dan kecepatan fluida yang digunakan pada CFD adalah 4m/s.